Myasthenia gravis and thymoma: evaluation of 41 patients Miastenia grave e timoma: avaliação de 41 pacientes - JOSÉ LAMARTINE DE ASSIS; ANTONIO ALBERTO ZAMBON; PATRICIA S. SOUZA; PAULO EURIPEDES MARCHIORI (Arquivos de Neuro-Psiquiatria)
We evaluated the epidemiological, clinical, laboratory and therapeutical aspects of 41 patients with thymomatous myasthenia gravis. Thirty five patients (85.36%) were submitted to thymectomy. Follow-up ranged from two to 18 years. Diagnosis of thymoma was based upon clinical investigations and CT scan of the anterior mediastinum and in 11 patients supported by immunological tests of anti-striated muscle antibodies with a positive result in more than 80% of cases. Histopathologic examination of all thymomectomized patients confirmed the diagnosis of thymoma. There was a significant predominance of benign over malignant thymoma. Occurred higher prevalence of male patients and of patients over 40 years of age. The therapeutical strategy to control myasthenic clinical findings was the same as that for non-thymomatous myasthenia gravis. The corticosteroids associated to cytotoxic drugs were less often used. Radiotherapy of the anterior mediastinum was more often used in patients having invasive tumors submitted to surgery or not. With regard to survival and control of myasthenia gravis, especially in younger patients and in those submitted to early surgery, results of treatment were surprisingly favorable. Avaliamos 41 pacientes com miastenia grave timomatosa sob os aspectos epidemiológico, clínico e terapêutico. Trinta e cinco pacientes (85,36%) foram timectomizados. O seguimento clínico variou de dois meses até 18 anos. O diagnóstico do timoma foi fundamentado no estudo de imagem do mediastino (tomografia axial computadorizada) e, em 11 pacientes, complementado com a determinação sérica de anticorpos para músculo estriado com resultado positivo em mais de 80% dos casos e confirmado pelo exame anátomo-patológico do timo realizado em todos os pacientes operados. Ocorreu predomínio significante de timomas benignos sobre timomas malignos, forma clínica generalizada severa, frequente envolvimento do sexo masculino e, em pacientes com mais de 40 anos de idade. A estratégia terapêutica para o controle dos sintomas miastênicos foi a mesma que para os pacientes não timomatosos. O emprego de imunossupressão medicamentosa esteróide associada a drogas citotóxicas foi menos frequente. A radioterapia foi usada com mais frequência nos pacientes portadores de tumores invasivos operados ou não.